FUNGSI PENGAWASAN BADAN PERMUSYAWARATAN DESA DALAM PENGGUNAAN ALOKASI DANA DESA DI DESA SUKABUDI KECEMATAN SUKAWANGI KABUPATEN BEKASI - Hafisha, Chintia; Suryani, Elvira (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2023)
The oversight function of the Village Consultative Body in the Use of Village Fund Allocations is the process by which village government activities can be carried out effectively and efficiently bypredetermined plans and provisions. The relationship between the BPD and the Village Head, who functions as a village partner between the legislature and the executive. Then, this partnership relationship is by Law Number 6 of 2014 concerning Villages which is manifested in the form of a BPD position that is equal to the Village Head. The form of this research is descriptive qualitative by explaining events or situations in a systematic, factual, and accurate manner concerning BPD supervision of the distribution of village funds in Sukabudi Village, Sukawangi District, Bekasi Regency. This data collection was carried out by observation, interviews, and a literature study. This theory uses Siagian's theory which states that there are two variables in the form of direct supervision and indirect supervision of the implementation of the Village Fund Allocation (ADD). The oversight function of the Village Consultative Body in the Use of Village Fund Allocations in Sukabudi Village, the BPD (Village Consultative Body) oversight in supervising ADD is quite good. However, some members of the BPD do not understand their duties and functions as members of the BPD. Like they are still ignoring their duties as overseers of village government activities. Then, there are problems with funding in 2022 where there are activities that have not been carried out due to being hampered by Covid-19 at that time. There is also the existence of obstacles that hinder the BPD in carrying out supervisory functions such as incompetent human resources and institutionally the BPD does not understand their duties and functions as members of the BPD. Still, there are supporting factors where the cooperative relationship between the village government is good, and there is also community participation that supports the village government. Then there is a strategy from the Sukabudi village government where there are many hopes that have not been implemented by the Sukabudi village government.